The keeper of secrets - Thomas, Julie, 1959- (William Morrow, 2013)
Following a priceless violin across five decades, this stunning debut novel tells the story of orchestra conductor Rafael Gomez who, inspired by the playing of an aspiring violin virtuoso who suddenly refuses to play another note, will do anything he can to change that.